Two models of contemporary public service wage determination in Australia - Hawkes, David (1999)
Rather than taking Louise Thornthwaile and Robyn Hollander (AJPA June 1998) to task, I need to chide them gently for failing to acknowledge two other jurisdictions in Australia - the Northern Territory and the Australian Capital Territory. Had they canvassed the Northern Territory's experience, they may well have concluded that there are in fact three models of public sector wage determination, not two. They may have also concluded that the Northern Territory's rather unique adaptation of the federal system under the Workplace Relations Act represents something more than an approach dictated by its relatively small size and that it arguably represents the best of both the other models. May I suggest that Thornthwaite and Hollander, or others, could usefully explore the question as to whether the approaches adopted by the various jurisdictions have produced worthwhile results for both employers and employees. - Reproduced
Keywords: Wages - Australia; Civil service - Australia; Civil service